Reliability of YouTube videos on robotic spine surgery for patient education. (March 2023) - Safa, Adrian; De Biase, Gaetano; Gassie, Kelly; Garcia, Diogo; Abode-Iyamah, Kingsley; Chen, Selby G.
Highlights: There should be an increased institutional oversight to combat the spread of medical misinformation. Three independent healthcare personnel evaluated the videos' education quality on robotic spin surgery using the validated DISCERN tool. YouTube videos on robotic spine surgery lack accuracy and have overall poor educational value. Abstract: Background: Robotic surgical systems developed to improve spine surgery accuracy. Studies have found significant reductions in screw revisions and radiation exposure with robotic assistance compared with open surgery. YouTube is the largest online video platform for medical education. Therefore, there is a need for the continuous critical assessment of healthcare-related YouTube videos. Our objective is to assess the reliability of YouTube videos on robotic spine surgery for patient education. Methods: In April of 2022, YouTube was queried for the following keywords: "Robotic Spine Surgery". The "Relevance-Based Ranking" filter was applied, and the first 3 result pages were considered. Videos had to be uploaded by universities or hospitals and be in the English. Three independent healthcare personnel evaluated the videos' education quality using the DISCERN tool. Results: Our study found that 33 % of videos analyzed scored above a 3 on the DISCERN scoring scale (considered a ''good" video), with overall mean DISCERN score of 2.8 ± 1.3 (SD). The duration of videos was significantly different between the two groups (Good = 16 min ± 21 vs Unhelpful = 4 min ± 4, p = 0.01 ). In the helpful group, other characteristics were number of views (16331 ± 31308), likes (88 ± 168) and dislikes (5 ± 8). No statistically significant differences were observed compared to the unhelpful group: number of views (6515 ± 9074; P = 0.20), likes (39 ± 55; P = 0.21) and dislikes (3 ± 4; P = 0.33). Conclusion: Our study shows that YouTube videos on robotic spine surgery lack accuracy and have poor educational value. There should be increased institutional oversight to combat the spread of misinformation.